The predictive value of phase angle on long-term outcome after ICU admission. Issue 6 (June 2022) - Stellingwerf, F.; Beumeler, L.F.E.; Rijnhart-de Jong, H.; Boerma, E.C.; Buter, H.
Summary: Introduction: The use of severity of illness scoring systems, including the Acute Physiology and Chronic Health Evaluation (APACHE) III score, has made it possible to compare groups of patients and evaluate treatment strategies. Phase angle, derived from bio-impedance analysis, reflects tissue quality and quantity in which cell mass, membrane integrity and hydration state are represented. We hypothesized that phase angle on ICU admission may serve as a proxy for physical frailty and as such can be used as an additional predictor of long-term mortality after ICU admission. Methods: A single-center prospective observational cohort study with consecutive patients, admitted to the ICU between June 2018 and June 2019. Demographic data, APACHE III, comorbidity, and phase angle in the first 6 h after ICU admission were collected and the ICU, hospital, and 1-year survival were registered. Results: Of all 1023 patients, 115 (11%) died within a year after ICU admission. Nonsurvivors had higher APACHE III scores than survivors [86 (65–119) vs. 55 (46–67), p < 0.001]. Phase angle was significantly higher in survivors than in nonsurvivors [5.4 (4.7–6.4) vs. 4.7 (3.9–6.0), p < 0.001]. Univariate analysis showed an association between mortality and admission type, sepsis, presence of malignancy, APACHE III, and PhA. Multivariate logistic regression analysis using these variables confirmed low PhA to be an independent predictor of 1-year mortality (OR: 1.81; CI: 1.09–2.97; p = 0.02), in addition to presence of malignancy (OR: 2.30; CI: 1.31–4.02; p = 0.004) and APACHE III score (OR: 1.03; CI: 1.02–1.04; p < 0.001). Conclusion: In this single center study, low phase angle was independently associated with 1-year all-cause mortality after ICU admission. ClinicalTrials.gov number: NCT0444976.